Correction: Dye-sensitized electron transfer from TiO2 to oxidized triphenylamines that follows first-order kinetics. Issue 6 (26th January 2018) - DiMarco, Brian N.; Troian-Gautier, Ludovic; Sampaio, Renato N.; Meyer, Gerald J.
Abstract : Correction for 'Dye-sensitized electron transfer from TiO2 to oxidized triphenylamines that follows first-order kinetics' by Brian N. DiMarco et al., Chem. Sci., 2018, DOI: 10.1039/c7sc03839a.